Peran Pembentukan Komite Sosial Kesetaraan Gender Perempuan dalam Isu Stereotip - Dinda Ayu Wardhani; Putri Maulina (Publikasi Indonesia, 2022)
The issue of gender inequality in the work environment such as gender stereotypes often occurs, one of which is at PT. Perkebunan Nusantara IV Bah Butong Tea Business Unit, where the workers were completely unaware of this action. This gender inequality arises because companies operating in industries or factories where the dominant workforce is male, thus causing gender inequality to be avoided. Employees must be able to balance position and power like male employees in every part of the job. In this study, the researcher uses a qualitative approach where Sugiyono (2016: 9) argues that qualitative research methods are used to examine proportional objects and the role of researchers as the main instrument in the research conducted. Gender inequality in the world of work does not see the position in the agency. Gender inequality cannot be overcome only by relying on position, work competence, or physical strength. The women's gender equality social committee was formed in order to provide impetus for change and address these issues. The company provides broad opportunities and fairness for women to develop their careers. Through the women's gender equality social committee forum, efforts for gender equality in the work environment continue to maximize and provide full support for the careers of female employees.